Effect Of The Reduction Temperature Into Catalytic Activity Of Ni Supported By Ti02, Al202 And Ti02/Al203 For Conversion Co2 Into Methane = Pengaruh Temperatur Reduksi Terhadap Aktivitas Katalis Ni Dengan... - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
ABSTRACT Nickel catalysts, containing 6% (w/w) of nickel, have been prepared using TiO2, A/203 and mixture of Ti02-A/203 (1:9). The catalysts were used for CO2 conversion into methane. The characteristics of catalysts were studied by determination of its specific surface area, temperature programmed reaction technique and X-ray diffraction. The specific surface area were varied slightly by different temperature of reduction, namely after reduction at 300°C it was 39, 120 and 113 m2/g and after reduction at 400°C it was 42, 135 and 120 m2/g for 6% nickel catalysts supported on Ti02, A/203 and mixture of TiOrAl203 (1:9) respectively. Temperature program reaction studies (TPO and TPR) showed that NiTiO, species were possibly formed during the pretreatments which has shown by the shift of its peak to the lower temperature on Ni catalyst, that supported on mixture of TiOrAl203 compared with catalysts supported on individual TiO2 or Al203. The nickel species on reduced Ni catalysts supported on TiO2and on mixture of Ti02-Al203 could be detected by X-ray diffraction. The catalyst's activities toward CH4 formation were affected by the reduction temperature. Activity for CH4 formation was decreased in the following order: Nil Ti02> Ti02: Al203> Nil Al203and Ni/ Ti02: Al203 > Ti02> Nil Al203, when catalysts were reduced at 300°C or 400°C respectively. The CO2 conversion was decreased in the following order: Nil A/203 > Ni/ Ti02: Al203> Nil TiO2 when catalysts were reduced at 300°C or 400°C respectively.